Remembering Eden the reception history of Genesis 3: 22-24 - Lanfer, Peter Thacher (New York Oxford Oxford University Press, 2012)
In this book, Peter Thacher Lanfer seeks to evaluate texts that expand and explicitly interpret the expulsion narrative of Adam and Eve in Genesis beyond the biblical canon
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc; Tree of life; Eden; Bible ; O.T ; Genesis III, 22-24 ; Criticism, interpretation, etc